Circ_0089761 accelerates colorectal cancer metastasis and immune escape via miR‐27b‐3p/PD‐L1 axis - Qizhong Gao; Xiaowei Cheng; Xiang Gao (Physiological Reports)
Abstract Circular RNAs have been implicated as critical regulators in the initiation and progression of colorectal cancer (CRC). This study was intended to elucidate the functional significance of the circ_0089761/miR‐27b‐3p/programmed cell death ligand 1 (PD‐L1) axis in CRC. Our findings indicated that circ_0089761 expression was significantly elevated in CRC tissues and cell lines. Furthermore, the high expression of circ_0089761 was correlated with TNM stage and tumor size. Silencing circ_0089761 inhibited CRC cell proliferation, migration, and invasion, and increased apoptosis. Mechanistically, circ_0089761 facilitated its biological function by binding to miR‐27b‐3p to upregulate PD‐L1 expression in CRC. Coculture experiments confirmed that low expression of circ_0089761 impeded CD8 + T cell apoptosis and depletion, activated CD8 + T cell function, and increased secretion of the immune effector cytokines IFN‐γ, TNF‐α, perforin, and granzyme‐B. MiR‐27b‐3p inhibition or PD‐L1 overexpression partially impeded CD8 + T cell function. The circ_0089761/miR‐27b‐3p/PD‐L1 axis is postulated to exert pivotal functions in the mechanistic progression of CRC. Furthermore, it holds promising prospects as a feasible biomarker and therapeutic target for CRC.